ANALISIS SIFAT FISIK DAGING SAPI TERDAMPAK LAMA PERENDAMAN DAN KONSENTRASI KENIKIR (Cosmos caudatus kunth) - Rohmah Rohmah; Mohammad Fuad Fauzul Mu’tamar; Umi Purwandari (Agroindustrial Technology, University of Trunojoyo Madura, 2018)
Beef is one of the most popular food commodities. Beef often has textural problems, especially when consumed. One method to improve the tenderness of beef is by enzymatic treatment. In some plants there are meat-eating enzymes. This study aims to determine the influence of leaves kenikir (cosmos caudatus kunth) against the tenderness of beef. The researchers used a complete randomized RAL design method with two factors each of the 3 levels of the first factor of leaf extract of kenikir with 25, 50, 75% concentration while the second factor was the immersion time of 15, 30 and 45 minutes. The test parameters included hardness, cooking shrinkage, power water tie and sensory (aroma, color, texture). The results showed that the texture test decreased the level of hardness of beef along with the increased concentration of the added leaves. Likewise with the long immersion, the longer the soaking results of the hardness of beef being tried further decreased.